3D motion retrieval based on double index and user interaction. (1st January 2013) - Jian, Xiang
In this paper, a novel method based on double index with content-based characteristic index and user interaction is presented to provide a flexible and effective 3D motion retrieval and control. Experimental results show that our method can overcome the limitations of conventional method of motion retrieval and improve the retrieval accuracy.